Perinatal Management for a Pregnant Woman with an MYH9 Disorder - Yuka Yamashita; Rei Matsuura; Shinji Kunishima; Yoshie Oikawa; Hirotsugu Ariizumi; Shoko Hamada; Nahoko Shirato; Ryu Matsuoka; Kohichi Ogawa; Akihiko Sekizawa (Case Reports in Obstetrics and Gynecology)
We diagnosed a primipara woman with an MYH9 disorder during her pregnancy. A peripheral blood smear with an immunofluorescence analysis is the established method of diagnosing MYH9 disorders. We provided genetic counseling, as required, which included apprising the woman of the inheritance pattern, the importance of a genetic analysis, and the potential delivery risks for the patient and her offspring. Given that the potential delivery risks are reportedly low, special perinatal management is not necessary for patients with an MYH9 disorder whose platelet count is above 5.0 × 104/μL, except for rapid blood access.